Partially methylated alleles, microdeletion, and tissue mosaicism in a fragile X male with tremor and ataxia at 30 years of age: A case report. Issue 12 (1st October 2016) - Hwang, Yun Tae; Aliaga, Solange Mabel; Arpone, Marta; Francis, David; Li, Xin; Chong, Belinda; Slater, Howard Robert; Rogers, Carolyn; Bretherton, Lesley; Hunter, Matthew; Heard, Robert; Godler, David Eugeny
Abstract : CGG repeat expansion >200 within FMR1, termed full mutation (FM), has been associated with promoter methylation, consequent silencing of gene expression and fragile X syndrome (FXS)—a common cause of intellectual disability and co‐morbid autism. Unmethylated premutation (55–199 repeats) and FM alleles have been associated with fragile X related tremor/ataxia syndrome (FXTAS), a late onset neurodegenerative disorder. Here we present a 33‐year‐old male with FXS, with white matter changes and progressive deterioration in gait with cerebellar signs consistent with probable FXTAS; there was no evidence of any other cerebellar pathology. We show that he has tissue mosaicism in blood, saliva, and buccal samples for the size and methylation of his expanded alleles and a de novo, unmethylated microdeletion. This microdeletion involves a ∼80 bp sequence in the FMR1 promoter as well as complete loss of the CGG repeat in a proportion of cells. Despite FMR1 mRNA levels in blood within the normal range, the methylation and CGG sizing results are consistent with the diagnosis of concurrent FXS and probable FXTAS. The demonstrated presence of unmethylated FM alleles would explain the manifestation of milder than expected cognitive and behavioral impairments and early onset of cerebellar ataxia. Our case suggests that individuals with FXS, who manifest symptoms of FXTAS, may benefit from more detailed laboratory testing. © 2016 Wiley Periodicals, Inc.